Prison Break. Education of young adults in closed prisons—building a bridge from prison to civil society?. Issue 2 (3rd April 2018) - Mertanen, Katariina; Brunila, Kristiina
ABSTRACT: Prison education is seen in both criminal and education policies as a way of assimilating inmates 'back into society'. In spite of the policy emphasis on education, the practices in prison education vary from prison to prison. The stated aim of prison education in EU and in Finnish national level policies is to teach inmates the skills and knowledge that they can use in life after release and thus reduce recidivism. In this paper, we analyse policies and practices related to education programmes in closed prisons in Finland with discourses of employability and therapisation of education. International and national policy documents and ethnographic data and interviews with young people and teachers have been use as data sources. Our aim is to draw a picture of multiple and complex power relations that shape the young adults in prison as flexible subjects that are able to make the transition from prison 'back' to civil society.